Condições necessárias para estabilidade de difeomorfismos - Amorim, Antonio Gomes de (1978)
This work has as main objective to study the conditions necessary for a diffeomorphism of a differentiable variety M to be omega-stable and is based on the work of John Frank "Necessary Conditions for Stability of Diffeomorphisms". This monograph is divided into three sections. The first section sets out some basic concepts in Dynamic Systems which are indispensable to subsequent ones. In section II, we will show that every pariodic point of an omega-stable diffeomorphism is hyperbolic. Section III is devoted to the stable varieties of an omega-stable diffeomorphism on a differentiable variety M.